Physical chemical characterization of thermally and aqueous solution treated maize stalk stem ash and its potential use in a cementing system. Issue 8 (17th April 2020) - Feng, Guorui; Qi, Tingye; Xu, Guang; Zhang, Dongsheng; Wang, Zehua; Li, Zhen
ABSTRACT: This study focused on evaluating the composition structure and morphology of maize stalk stem ash (MSSA) produced after treatment at 500, 700 and 850°C calcination temperatures and after undergoing an aqueous solution treatment. This study also investigated the possibility of using MSSA in a cementing system. The grain size distribution, chemical composition and microstructure of MSSA were investigated by Laser Mastersizer, X-ray fluorescence (XRF) and scanning electron microscope (SEM). The MSSA samples obtained before and after aqueous solution treatment were analyzed using X-ray powder diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) to determine the Si 2p transformation behavior. The zeta potential, pH value and conductivity of the hybrid solution were tested along with the dissolving time. The grain size of MSSA was closer to the continuous gradation with increasing calcination temperatures. The dominant composition of the silica and potassium oxide were observed in the MSSA. The pH value, conductivity and zeta potential at 700°C were high compared to those at the other calcination temperatures at a certain dissolving time. A higher nucleation degree of MSSA with an increasing calcination temperature was observed by micromorphology. The presence of crystalline SiO2 was identified in MSSA-500 and MSSA-700, but not in MSSA-850. Silica was deposited on the surface of the MSSA in the form of Si-O-Si and Si-OH from the XPS spectra.